School and class-level variations and patterns of physical activity: a multilevel analysis of Danish high school students - Carina Bjørnskov Steenholt; Veronica Sofie Clara Pisinger; Ida Høgstedt Danquah; Janne Schurmann Tolstrup (BMC, 2018)
Abstract Background There is limited knowledge of physical activity (PA) patterns among high school students. High schools plays an important role as context for the students, but it is uncertain to what extent schools influence student participation in PA during leisure time. The purpose of this study is to describe patterns of PA and assess variations between schools and classes in PA, in a large cohort of Danish high school students. Methods Self-reported cross-sectional data came from The Danish National Youth Study, comprising a total of 70,674 students attending 119 different schools and 3213 classes. Multilevel logistic regressions were applied to evaluate the association between socio-demographic variables and patterns of PA, and to assess the impact of schools and classes on PA measures. Results Students whose parents have achieved a lower level of education, older students and girls of perceived ethnic minority generally participated less in several forms of PA during leisure time. Substantial variations between schools were observed in terms of participation in PA at school during leisure time and in terms of use of active transportation to and from school. The school-level accounted for 9% (intra-class correlation coefficient (ICC) = 0.09 (95% CI: 0.06-0.11)) and 8% (ICC = 0.08 (95% CI: 0.07-0.11)) of the variation for participation in PA during leisure time and active transportation. Conclusion Overall, students whose parents achieved a lower level of education, older students and girls of perceived ethnic minority represent vulnerable groups in relation to participation in several forms of PA during leisure time. The ICCs indicate that schools, in particular, have the potential to influence participation in PA at school during leisure time and active transportation to and from school. Thus, high schools should encourage and facilitate activities aimed at engaging students in PA during leisure time as well as encourage active transportation.